B-type natriuretic peptide in the evaluation of cardiac function - Adriana Polachini do Valle; Paulo José Fortes Villas Boas; Edison Iglesias de Oliveira Vidal; Fernanda Bono Fukushima (Sociedade Brasileira de Patologia Clínica, 2013)
B type natriuretic peptide (BNP) and its precursor, the inactive form of NT-pro-BNP, are currently the most studied laboratory parameters in the heart disease spectrum. The assessment of their blood concentrations provides invaluable information on the likelihood, severity and prognosis of the disease. The present review aims to describe the biological determinants, the factors that influence these peptide concentrations, the suggested cutoff values for the diagnosis of heart failure and the use of this biomarker in the assessment of cardiac function.